DAMPAK PEMEKARAN TERHADAP PELAYANAN PUBLIK DI KELURAHAN TUAH MADANI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2018 - Govinda Xaverius; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tuah Madani was expanded On 2015. Taking into account the criteria for economic capacity, regional potential, socio-cultural conditions, socio-political conditions, population size, area, and other considerations, Tuah Madani was formed. As for the formulation of the problem in this study, that is : First, what is the impact of expansion on public services in Tuah Madani, Tampan, Pekanbaru City on 2018. Second, what are the inhibiting factors in the impact of expansion on public services in Tuah Madani, Tampan, Pekanbaru City on 2018. As for the purpose of writing this thesis, that is : First, to determine the impact of expansion on public services in Tuah Madani, Tampan, Pekanbaru City on 2018. Second, to find out what are the inhibiting factors in the impact of expansion on public services in Tuah Madani, Tampan, Pekanbaru City on 2018. This study used the qualitative research. This research was conducted at the Tuah Madani Village Office, Tampan. The techniques used to collect data in this study were (1) interview, (2) observation, and (3) document search.               The conclusion of this researched shows that the impact of post-expansion public services in Tuah Madani, Tampan, has not been running optimally, this shows that after the expansion, the quality of the services provided according to the views of the community in Tuah Madani, the authors suggest that there should be an active role of government. which is represented by the sub-district office or an office at the same level as above to always provide supervision. Keywords: Service Operational Standards, Ease of Service, Quality of Public Services